Bacteremic purulent knee arthritis caused by a non-toxigenic strain of Corynebacterium diphtheriae - Istomin, Kostiantyn; Balejová, Magda; Dvořáková, Eva; Musil, David; Klouda, Jan; Chrdle, Aleš (Klinicka mikrobiologie a infekcni lekarstvi, 2023)
Corynebacteria, non-spore-forming, gram-positive, aerobic or facultative anaerobic, pleomorphic bacilli, are part of the normal skin, oropharyngeal, and intestinal flora in humans. However, this microorganism can rarely be associated with invasive infections such as bone and joint infections, bacteremia, endocarditis, meningitis, liver and spleen abscesses. We present a case of bacteremic arthritis of a native knee joint caused by non-toxigenic Corynebacterium diphtheriae in a patient with alcoholic liver cirrhosis. This case report emphasizes the importance of differential diagnosis and careful examination of immunocompromised patients and reviews the criteria for administration of C. diphtheriae antitoxin in case of invasive disease.
Keywords: Diphtheria; Arthritis, Infectious; infekční artritida; alkoholická cirhóza jater; Bacteremia; Humans; kolenní kloub; bakteriemie; Liver Cirrhosis, Alcoholic; difterie; Knee Joint; lidé; Corynebacterium diphtheriae